The Potential of Community Radio in Fostering Economic Empowerment of Youths in The Cape Flats Communities - Joseph Olusegun Adebayo; Gqibile John Bulani; Trust Matsilele (Communicare : Journal of Communication Studies, 2022)
This study examines the role community radio plays in fostering the economic empowerment of youths in the Cape Flats. Using Bush Radio as a case study, the researchers theoretically anchored the study on Dennis McQuailâ€™s (1987) media development theory. The study population comprised management staff, presenters, and listeners of Bush Radio. Findings revealed that Bush Radio positions youth at the forefront of their programming.  The station serves as a credible source of information relevant and beneficial to young people focusing on entrepreneurship, financial literacy, education, and employment creation. Findings reveal that the stationâ€™s youth-centric programmes focus on crucial community media tenets of localism and participation, which affords local young talent of artists a platform to promote and monetise their creative material. Finally, some of the studyâ€™s findings revealed the station acts as a conduit that connects youths with government and relevant organisations offering opportunities to uplift and better their livelihoods.